Feeding and oviposition behaviour of the cocoa mirids Helopeltis theivora Waterhouse - Muhamad R. (Malaysian Plant Protection Society, 2018)
This paper describes research on some aspects of feeding and oviposition behaviour of the cocoa mirids, Helopetis theivora Waterhouse. Field and laboratory experiments were conducted in the study. Results obtained showed that H. theivora preferred small cocoa pods (about 4 to 8 cm long pods) since more feeding lesions and eggs were laid per unit area of surface on those pods than on bigger pods (8 to 16 cm long pods). It was also observed that very few feeding lesions and eggs were found on the smallest cherelles (less than 4 cm long). It is suggested that the female chooses to ovipositon relatively old cherelles and young pods because its nymphs may benefit by feeding during a nutritious growing phase of pod development. The study also revealed that females preferred to lay their eggs in or close to feeding lesions. Male adults did not make feeding lesions where an egg was laid earlier. The females always feed before laying eggs and they did not lay any eggs when their stylets were removed.